Program Pojok Baca Untuk Meningkatkan Literasi Anak Usia Dini Di TK Tunas Harapan Desa Dahor Grabagan Tuban - Niswatin Ni’matuthoyyibah; Susiyati Novitasari; Ummidlatus Salamah (Institut Agama Islam Nahdlatul Ulama Tuban, 2022)
Abstract: This research aims to identify and describe the function and role of the reading corner in improving early childhood literacy at Tunas Harapan Kindergarten in Dahor Village, Grabagan District, Tuban Regency. Improving literacy culture in children needs to be instilled from an early age. Children must have a literacy culture from an early age, said the Director of Early Childhood Education (PAUD) of the Ministry of Education, Culture, Research and Technology (Kemendikbudristek), Muhammad Hasbi. However, learning literacy still has to be adapted to the child's growth and development. Through this service, the service team made the reading corner a vehicle to foster reading interest for children at Tunas Harapan Kindergarten, Dahor Village. Activities in making this class reading corner are carried out by a service team, starting from preparing a class which will later be made a class reading corner, the materials needed in making a reading corner. The final result of this activity is expected that the reading corner that has been made will make children enthusiastic and active in reading. The data collection techniques used in this study were observation, interviews, and documentation.